Retrospective study of 33 dogs diagnosed with osteosarcoma (OSA) by fine needle aspiration cytology (FNAC) at FMVZ vet hospital, UNESP-Botucatu, SP - Wilmsen, Maurício Orlando [UNESP]; Tremori, Tália Missen [UNESP]; Rocha, Noeme Sousa [UNESP] (Sciencedomain International, 2016)
Aim of Study: Evaluate cases of dogs with osteosarcoma, when diagnoses using FNAC. Study Design: A retrospective study, from archive at Veterinary Hospital, selected 33 dogs of different races, 23 females (69.6%) and 10 males (30.3%) were addressed, the age of tested dogs ranged from 1 to 15 years, with diagnoses of osteosarcoma using FNAC. These animals are classified according to localization of tumor, cytopathology evaluation and radiography exam. Results: In this study, a general OSA prevalence on appendicular skeleton of 90.9% (30), being humerus and axial skeleton 9.1% (3). Likewise, the highest age incidence ranged from 6 to 15 years (78.7%). 33 of 24 animals (72.7%) had tumor complications in forelimbs discriminated from high to low incidence: 17 (51.5%) left forelimbs (LFL,) and 7 (27.3%) right forelimbs (RFL). Cancer signs also appeared in axial skeleton of 2 individuals (6.5%), and paranasal sinus of another (3.2%). Cytoplasmic and nuclear characteristics showed atypical mitosis in 31 (93.9%), and multinucleated cells in 33 (100%) on evaluated specimens. Conclusion: The use of FNAC demonstrated to be a simple, quick, efficient, minimally invasive, and inexpensive diagnostic tool.
Keywords: Bone neoplasm; Canine; Fine-needle aspiration cytology (FNAC)